2002
DOI: 10.1590/s1519-566x2002000200005
|View full text |Cite
|
Sign up to set email alerts
|

La comunidad de arañas del cultivo de soja en la provincia de Buenos Aires, Argentina

Abstract: The spiders are one of the most important predators that produce the mortality of the plague insects. The spider community was sampled with nets, plant pocketed and pit fall traps on soybean crop and the wild vegetation on the borders (2h manual capture). The samples are done during the crop development (December to mid-May) and, in the fallow period (mid-May to November), in order to know spiders specific composition, to compare specific diversity through Shannon index, and, to analyze the colonization proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1
31

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 17 publications
6
23
1
31
Order By: Relevance
“…These results are not compatible with those reported by Minervino (1996) and Liljesthrom et al (2002), who found Thomisidae to represent about 50%. The discrepancy might be due to: 1) a different sampling method; these authors placed plants in individual plastic bags and probably the results could have been masked because of the reduced size of the Oxyopidae individuals; 2) different seeding method; they used conventional seeding, which has destructive effects on the soil, whereas in the present work, soil conditions were not altered because of the direct seeding method; 3) different climatic conditions (mid-south Buenos Aires province vs. mid-west Santa Fé province).…”
Section: Spider Families Found In the Soybean Cropcontrasting
confidence: 99%
See 4 more Smart Citations
“…These results are not compatible with those reported by Minervino (1996) and Liljesthrom et al (2002), who found Thomisidae to represent about 50%. The discrepancy might be due to: 1) a different sampling method; these authors placed plants in individual plastic bags and probably the results could have been masked because of the reduced size of the Oxyopidae individuals; 2) different seeding method; they used conventional seeding, which has destructive effects on the soil, whereas in the present work, soil conditions were not altered because of the direct seeding method; 3) different climatic conditions (mid-south Buenos Aires province vs. mid-west Santa Fé province).…”
Section: Spider Families Found In the Soybean Cropcontrasting
confidence: 99%
“…These traps consisted of 8 cm x 10 cm plastic containers, one fourth filled with ethylene glycol 30%, as a preserver. Forty traps were buried, at a rate of 5 equidistant traps in every margin; the remaining 20 traps were distributed in the same way within the crop (Liljesthrom et al, 2002). All captured material was preserved in 70 % ethyl alcohol to be identified at the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations